Penerapan Altman Z-Score Modifikasi Dalam Memprediksi Kebangkrutan PT Matahari Department Store Tbk Periode 2018-2022 - Sari, Putri Adita; Nurlinda, Nurlinda (Universitas Medan Area, 2024)
This final report is entitled “The Implementation of Altman Z-Score Modification in Predicting Bankruptcy PT Matahari Department Store Tbk for the period of 2018-2022”.The purpose of this final report is to determine the prediction of bankruptcy at PT Matahari Department Store Tbk for the 2018-2022 period using the Altman Z-Score method. The population of this final report is the financial statements of PT Matahari Department Store Tbk and the sample of this final report is the financial statements of PT Matahari Department Store Tbk for the period 2018-2022. The type of data used is quantitative data and the data source used is secondary data. Data collection techniques use documentation from financial statements published through www.matahari.com website. Data processing techniques using the Altman Z-Score Modification formula with descriptive statistics analysis techniques. Based on the results of data processing, the Z-Score result in 2018 was 6,498; in 2019 it was 6.8738; the year 2020 was -0.1909; in 2021 it was 3.4049; Year 2022 is 3.4933. Based on data analysis, it can be concluded that PT Matahari Department Store Tbk for the 2018, 2019, 2021, and 2022 periods is included in the safe zone because the standard assessment indicator is Z 2.6, while in 2020 it is included in the dangerous zone indicator because the Z-Score value is at Z 1.1.